Anais Do XXVIII Simpósio Brasileiro De Informática Na Educação (SBIE 2017) 2017
DOI: 10.5753/cbie.sbie.2017.51
|View full text |Cite
|
Sign up to set email alerts
|

Off-Topic Essay Detection: A Systematic Review

Abstract: Abstract. Essays are widely used for learning assessment in the educational

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…This study addresses the detection of essays from unexpected prompt, which can be seen as a task of analyzing the textual similarity between the essay and the prompt statement (Higgins et al, 2006). In the existing literature, off-topic essay detection has been performed by applying techniques of natural language processing, semantic analysis and linguistics features, such as essay length, organization, and sentence variety (Passero et al, 2017).…”
Section: Off-topic Essay Detectionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study addresses the detection of essays from unexpected prompt, which can be seen as a task of analyzing the textual similarity between the essay and the prompt statement (Higgins et al, 2006). In the existing literature, off-topic essay detection has been performed by applying techniques of natural language processing, semantic analysis and linguistics features, such as essay length, organization, and sentence variety (Passero et al, 2017).…”
Section: Off-topic Essay Detectionmentioning
confidence: 99%
“…A previous systematic review of the literature identified five articles, published between 2006 and 2016, which present one or more approaches for off-topic essay detection (Passero et al, 2017). In this comparative study, these approaches were considered to represent the state of the art, together with the approaches presented by Klebanov, Flor, & Gyawali (2016) and Rei & Cummins (2016), which were found to be relevant and adaptable to the task of off-topic essay detection.…”
Section: Off-topic Essay Detectionmentioning
confidence: 99%
See 3 more Smart Citations